Fe3O4-Fe3Se4 electrode material with composite structure and preparation method of Fe3O4-Fe3Se4 electrode material

Synthesis of Fe3O4@Fe3Se4 electrode material through hydrothermal method and calcination method, solving the problems of poor conductivity of Fe3O4 and structural phase change, improving the sodium storage capacity and cycle stability of sodium ion batteries, and achieving more efficient ion transfer and charge transfer .

CN119170757APending Publication Date: 2024-12-20CHANGSHU INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410770559.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-06-14
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

As the negative electrode material of sodium ion battery, Fe3O4 has poor conductivity and structural phase change problems, resulting in a degradation of cycling performance.

Method used

The Fe3O4@Fe3Se4 electrode material with composite structure is synthesized by hydrothermal method and calcination method. By controlling the molar ratio of iron source and selenium source, an intrinsic electric field is formed to accelerate ion transfer and charge transfer, and the conductivity and electrical conductivity of Fe3O4 are improved through Fe3Se4. Chemical activity.

Benefits of technology

It improves the sodium storage capacity and reaction kinetics of Fe3O4, enhances the cyclic stability and conductivity of the electrode material, and improves the performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170757A_ABST
    Figure CN119170757A_ABST
Patent Text Reader

Abstract

The invention discloses a Fe3O4-coated Fe3Se4 electrode material with a composite structure and a preparation method of the Fe3O4-coated Fe3Se4 electrode material. The preparation method comprises the following steps: (1) preparing a solution; (2) hydrothermal reaction; and (3) high-temperature calcination. The Fe3O4-Fe3Se4 electrode material with a composite structure is synthesized by regulating and controlling the molar ratio of an iron source to a selenium source and utilizing hydrothermal reaction and high-temperature calcination, and Fe3Se4 has relatively high conductivity and relatively good electrochemical activity, so that the volume change of a Fe3O4 electrode can be relieved, and the sodium storage capacity of Fe3O4 is improved. Besides, an internal electric field is formed in the Fe3O4-coated Fe3Se4 composite structure, so that ion transmission and charge transfer of Fe3O4 can be accelerated, and the reaction kinetics of the Fe3O4 can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a Fe3O4@Fe3Se4 electrode material with a composite structure and a preparation method thereof. Background Art

[0002] Sodium-ion batteries play an indispensable role in the field of energy storage due to their low cost and abundant sodium resources. + Large ionic radius leads to poor electrochemical performance of commercial graphite electrodes due to the difficulty in forming sodium-graphite intercalation compounds. Low specific capacity, poor rate capability, and sluggish kinetics have become bottleneck problems faced by carbon-based materials in practical applications. Therefore, it is of great significance to develop sodium-ion battery anode materials with high capacity and fast kinetics.

[0003] Due to its high theoretical specific capacity (>900mAh / g), abundant reserves, low price, and environmental friendliness, Fe3O4 has become a potential negative electrode material for sodium ion batteries. Fe3O4 electrode materials undergo redox reactions during sodium storage, and the reaction product Fe will cause large structural and volume changes, resulting in a decrease in cycle performance. At the same time, Fe3O4 itself has poor conductivity, which is not conducive to the rapid transmission of ions. Summary of the invention

[0004] In view of the problems of poor conductivity and large structural phase change of transition metal oxide Fe3O4 as a negative electrode material for sodium ion batteries, the present invention provides a high-performance Fe3O4@Fe3Se4 negative electrode material for sodium ion batteries with a composite structure and a preparation method thereof.

[0005] In a first aspect, the present invention provides a method for preparing a Fe3O4@Fe3Se4 electrode material having a composite structure, comprising the following steps:

[0006] a. Disperse the iron source, selenium source and hydrazine hydrate into deionized water in sequence, and continue stirring for a certain period of time to obtain a uniform solution;

[0007] b. Transferring the above solution to a reaction vessel for hydrothermal reaction;

[0008] c. After the reaction, the Fe3O4@Fe3Se4@Se composite material was obtained after centrifugal filtration and vacuum drying;

[0009] d. The Fe3O4@Fe3Se4@Se composite material is calcined in a protective atmosphere to obtain a Fe3O4@Fe3Se4 electrode material with a composite structure.

[0010] Preferably, in step a, the iron source is one or more of ferric chloride, ferric nitrate, ferrous chloride and ferrous nitrate.

[0011] Preferably, in step a, the selenium source is one or more of selenium dioxide, sodium selenate, selenic acid and selenium powder.

[0012] Preferably, in step a, the molar ratio of the iron source to the selenium source is 2:(1-3).

[0013] Preferably, in step a, the ratio of hydrazine hydrate to iron source is 2 mmol:(5-15 ml).

[0014] Preferably, in step b, the hydrothermal reaction temperature is 160-200° C. and the reaction time is 12-24 h.

[0015] Preferably, in step d, the protective atmosphere is any one of nitrogen, argon, argon-hydrogen mixed gas, etc.

[0016] Preferably, in step d, the calcination temperature is 400±20° C. and the calcination time is 2 to 4 hours.

[0017] In a second aspect, the present invention provides a Fe3O4@Fe3Se4 electrode material having a composite structure prepared by the method described in the first aspect.

[0018] In a third aspect, the present invention provides the use of the Fe3O4@Fe3Se4 electrode material with a composite structure prepared by the method described in the first aspect as a sodium ion negative electrode material.

[0019] Compared with the prior art, the present invention has the following beneficial effects: the present invention adopts a simple hydrothermal method and calcination method, and successfully synthesizes a Fe3O4@Fe3Se4 electrode material with a composite structure by controlling the molar ratio of the iron source and the selenium source. Compared with Fe3O4, Fe3Se4 has higher conductivity and better electrochemical activity, which can improve the sodium storage capacity of Fe3O4. At the same time, the intrinsic electric field formed in the Fe3O4@Fe3Se4 composite structure can accelerate the ion transmission and charge transfer of Fe3O4, and improve its reaction kinetics. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD diagram of the Fe3O4@Fe3Se4 electrode material with a composite structure prepared in Example 1.

[0021] Figure 2 This is the XRD pattern of the Fe3O4 electrode material obtained in Example 4.

[0022] Figure 3 This is the XRD pattern of the FeSe2 electrode material obtained in Example 5.

[0023] Figure 4 The cycling performance diagrams of the Fe3O4@Fe3Se4 electrode material with a composite structure prepared in Example 1, the Fe3O4 electrode material prepared in Example 4, and the FeSe2 prepared in Example 5. DETAILED DESCRIPTION

[0024] The present application is further described below in conjunction with specific embodiments.

[0025] It should be noted that the terms such as "upper", "lower", "left", "right", "middle", etc. cited in this specification are only for the convenience of description and are not used to limit the scope of implementation. Changes or adjustments to their relative relationships should be regarded as the scope of implementation of this application without substantially changing the technical content.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which this application belongs; the term "and / or" used herein includes any and all combinations of one or more of the associated listed items.

[0027] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.

[0028] As used herein, the term "about" is used to provide flexibility and imprecision associated with a given term, measurement or value. The degree of flexibility for a particular variable can be easily determined by one skilled in the art.

[0029] As used herein, the term "at least one of" is intended to be synonymous with "one or more of." For example, "at least one of A, B, and C" expressly includes only A, only B, only C, and combinations of each thereof.

[0030] Concentration, amount and other numerical data can be presented in range format herein.It should be understood that such range format is only used for convenience and simplicity, and should be flexibly interpreted as not only including the numerical value clearly described as range limit, but also including all single numerical values ​​or sub-ranges contained in the range, just as each numerical value and sub-range are clearly described.For example, the numerical range of about 1 to about 4.5 should be interpreted as not only including the limit value of 1 to about 4.5 clearly described, but also including single numerals (such as 2,3,4) and sub-ranges (such as 1 to 3,2 to 4, etc.).The same principle is applicable to the scope of only narrating a numerical value, such as "less than about 4.5", which should be interpreted as including all the above-mentioned values ​​and ranges.In addition, no matter how the breadth of the described range or feature is, this explanation should be applicable.

[0031] Metal selenides have good electrical conductivity, and their narrow energy gap is conducive to electron migration. In addition, selenium has a larger radius than oxygen and sulfur, so the metal-selenium bond is relatively easy to break, thereby accelerating the kinetics of the conversion reaction. The present invention first synthesizes the Fe3O4@Fe3Se4@Se composite material by a hydrothermal method, and then sinters it in an inert atmosphere to remove the elemental Se element, thereby constructing a Fe3O4@Fe3Se4 composite structure, and establishing an intrinsic electric field in the Fe3O4 crystal structure, which can accelerate ion transmission and charge transfer, improve the reaction kinetics of the electrode, and the presence of Fe3Se4 can alleviate the volume change of the Fe3O4 electrode and improve the cycle stability of the electrode material. The present invention mainly introduces the Fe3Se4 phase by a liquid phase method to improve the sodium storage capacity of Fe3O4, which is essentially different from the traditional method of using selenium powder or preparing selenium-doped Fe3O4 electrode materials by a solid phase method, and does not use selenium doping to improve the sodium storage capacity of Fe3O4.

[0032] Example 1

[0033] Add 2mmol ferric chloride (FeCl3·6H2O), 2mmol selenium dioxide (SeO2) and 5ml hydrazine hydrate (N2H4·H2O, 80%) to 35ml solution in sequence. After stirring for 1h, put the 50ml reactor containing the above substances into an oven, heat to 180℃, and keep warm for 24h. After the reaction is completed, wash the product repeatedly with deionized water, and then vacuum dry it in a 60℃ drying oven for 12h to obtain a Fe3O4@Fe3Se4@Se composite material. The above composite material was calcined at 400℃ in a nitrogen atmosphere for 2h with a heating rate of 5℃ / min to obtain a composite structure Fe3O4@Fe3Se4 electrode material, and its XRD is as follows Figure 1 shown.

[0034] The present invention uses a composite Fe3O4@Fe3Se4 electrode material as the negative electrode, a metal sodium sheet as the counter electrode, Whatman glass fiber (GF / D) as the separator, and a 1 mol / L NaClO4 / PC+5% FEC solution as the electrolyte. A CR2032 type button battery is assembled in a glove box protected by argon. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is carried out at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The cycle performance is as follows: Figure 4 As shown, the first discharge capacity of the composite Fe3O4@Fe3Se4 electrode material is 648.5 mAh / g, and the discharge capacity remains at 300.1 mAh / g after 100 cycles.

[0035] Example 2

[0036] 2mmol ferric chloride (FeCl3·6H2O), 1mmol selenium dioxide (SeO2) and 5ml hydrazine hydrate (N2H4·H2O, 80%) were added to 35ml solution in sequence. After stirring for 1h, the 50ml reactor containing the above substances was placed in an oven, heated to 180℃, and kept warm for 24h. After the reaction was completed, the product was repeatedly washed with deionized water, and then vacuum dried in a 60℃ drying oven for 12h to obtain a Fe3O4@Fe3Se4@Se composite material. The above composite material was calcined at 400℃ in a nitrogen atmosphere for 1h, with a heating rate of 5℃ / min, to obtain a Fe3O4@Fe3Se4 electrode material with a composite structure.

[0037] The present invention uses a composite Fe3O4@Fe3Se4 electrode material as a negative electrode sheet, a metal sodium sheet as a counter electrode, a Whatman glass fiber (GF / D) as a diaphragm, and an electrolyte of 1 mol / L NaClO4 / PC+5% FEC solution, and assembles a CR2032 button battery in a glove box filled with argon protection. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is performed at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The composite Fe3O4@Fe3Se4 electrode material has an initial discharge specific capacity of 589.1mAh / g, and after 100 cycles, the discharge specific capacity remains at 268.6mAh / g.

[0038] Example 3

[0039] 2mmol ferric chloride (FeCl3·6H2O), 3mmol selenium dioxide (SeO2) and 5ml hydrazine hydrate (N2H4·H2O, 80%) were added to 35ml solution in sequence. After stirring for 1h, the 50ml reactor containing the above substances was placed in an oven, heated to 180℃, and kept warm for 24h. After the reaction was completed, the product was repeatedly washed with deionized water, and then vacuum dried in a 60℃ drying oven for 12h to obtain a Fe3O4@Fe3Se4@Se composite material. The above composite material was calcined at 400℃ in a nitrogen atmosphere for 3h, with a heating rate of 5℃ / min, to obtain a Fe3O4@Fe3Se4 electrode material with a composite structure.

[0040] The present invention uses a Fe3O4@Fe3Se4 electrode material with a composite structure as a negative electrode sheet, a metal sodium sheet as a counter electrode, a Whatman glass fiber (GF / D) as a diaphragm, and an electrolyte of 1 mol / L NaClO4 / PC+5% FEC solution, and assembles a CR2032 type button battery in a glove box filled with argon protection. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is performed at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The first discharge specific capacity of the Fe3O4@Fe3Se4 electrode material with a composite structure is 500.7mAh / g, and the discharge specific capacity remains at 229.2mAh / g after 100 cycles.

[0041] Example 4

[0042] 2mmol ferric chloride (FeCl3·6H2O) and 5ml hydrazine hydrate (N2H4·H2O, 80%) were added to 35ml solution in sequence. After stirring for 1h, the 50ml reactor containing the above substances was placed in an oven, heated to 180℃, and kept warm for 24h. After the reaction, the product was repeatedly washed with deionized water, vacuum dried in a 60℃ drying oven for 12h, and then the obtained black substance was calcined at 400℃ in a nitrogen atmosphere for 2h, with a heating rate of 5℃ / min, to obtain Fe3O4 electrode material, whose XRD is as follows Figure 2 shown.

[0043] The present invention uses Fe3O4 electrode material as the negative electrode sheet, a metal sodium sheet as the counter electrode, Whatman glass fiber (GF / D) as the diaphragm, and an electrolyte of 1 mol / L NaClO4 / PC+5% FEC solution. A CR2032 type button battery is assembled in a glove box filled with argon protection. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is carried out at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The cycle performance is as follows: Figure 4 The first discharge capacity of the Fe3O4 electrode material is 561.8 mAh / g, and after 100 cycles, the discharge capacity remains at 31.6 mAh / g.

[0044] Example 5

[0045] 2mmol ferric chloride (FeCl3·6H2O), 4mmol selenium dioxide (SeO2) and 5ml hydrazine hydrate (N2H4·H2O, 80%) were added to 35ml solution in sequence. After stirring for 1h, the 50ml reactor containing the above substances was placed in an oven, heated to 180℃, and kept warm for 24h. After the reaction, the product was repeatedly washed with deionized water, and then vacuum dried in a 60℃ drying oven for 12h. Subsequently, the obtained black substance was calcined at 400℃ in a nitrogen atmosphere for 2h, with a heating rate of 5℃ / min, to obtain FeSe2 electrode material, whose XRD is as follows: Figure 3 shown.

[0046] The present invention uses FeSe2 electrode material as the negative electrode sheet, a metal sodium sheet as the counter electrode, Whatman glass fiber (GF / D) as the separator, and an electrolyte of 1 mol / L NaClO4 / PC+5% FEC solution. A CR2032 type button cell is assembled in a glove box filled with argon protection. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is carried out at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The cycle performance is as follows: Figure 4 The first discharge capacity of FeSe2 electrode material is 510.4 mAh / g, and the discharge capacity remains at 16.9 mAh / g after 100 cycles.

[0047] Example 6

[0048] 2mmol ferric chloride (FeCl3·6H2O), 2mmol selenium dioxide (SeO2) and 5ml hydrazine hydrate (N2H4·H2O, 80%) were added to 35ml solution in sequence. After stirring for 1h, the 50ml reactor containing the above substances was placed in an oven, heated to 180℃, and kept warm for 24h. After the reaction was completed, the product was repeatedly washed with deionized water, and then vacuum dried in a 60℃ drying oven for 12h to obtain a Fe3O4@Fe3Se4@Se composite material. The above composite material was calcined at 300℃ in a nitrogen atmosphere for 2h, with a heating rate of 5℃ / min, to obtain a Fe3O4@Fe3Se4 electrode material with a composite structure.

[0049] The present invention uses a Fe3O4@Fe3Se4 electrode material with a composite structure as a negative electrode sheet, a metal sodium sheet as a counter electrode, a Whatman glass fiber (GF / D) as a diaphragm, and an electrolyte of 1 mol / L NaClO4 / PC+5% FEC solution, and assembles a CR2032 type button battery in a glove box filled with argon protection. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is performed at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The first discharge specific capacity of the Fe3O4@Fe3Se4 electrode material with a composite structure is 229.2mAh / g, and the discharge specific capacity remains at 111.3mAh / g after 100 cycles.

[0050] Example 7

[0051] 2mmol ferric chloride (FeCl3·6H2O), 2mmol selenium dioxide (SeO2) and 5ml hydrazine hydrate (N2H4·H2O, 80%) were added to 35ml solution in sequence. After stirring for 1h, the 50ml reactor containing the above substances was placed in an oven, heated to 180℃, and kept warm for 24h. After the reaction was completed, the product was repeatedly washed with deionized water, and then vacuum dried in a 60℃ drying oven for 12h to obtain a Fe3O4@Fe3Se4@Se composite material. The above composite material was calcined at 600℃ in a nitrogen atmosphere for 2h, with a heating rate of 5℃ / min, to obtain a Fe3O4@Fe3Se4 electrode material with a composite structure.

[0052] The present invention uses a Fe3O4@Fe3Se4 electrode material with a composite structure as a negative electrode sheet, a metal sodium sheet as a counter electrode, a Whatman glass fiber (GF / D) as a diaphragm, and an electrolyte of 1 mol / L NaClO4 / PC+5% FEC solution, and assembles a CR2032 type button battery in a glove box filled with argon protection. Under a constant temperature environment of 25°C, a sodium negative electrode cycle test is performed at a current density of 0.1A / g and a cut-off voltage of 0.01-3.0V. The first discharge specific capacity of the Fe3O4@Fe3Se4 electrode material with a composite structure is 449.6mAh / g, and the discharge specific capacity remains at 274.5mAh / g after 100 cycles.

[0053] The above embodiments are merely preferred specific implementations of the present invention and are not intended to limit the scope of the present invention. Any modifications and improvements made to the technical solutions of the present invention by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A Fe with a composite structure 3 O 4 @Fe 3 Se 4 Method for preparing electrode materials, It is characterized in that The following steps are involved: a. Disperse the iron source, selenium source and hydrazine hydrate into deionized water in sequence, and continue stirring for a certain period of time to obtain a uniform solution; b. Transferring the above solution into a reaction kettle for hydrothermal reaction; c. After the reaction is completed, centrifuge and vacuum dry to obtain Fe 3 O 4 @Fe 3 Se 4 @Se composite materials; d. Fe 3 O 4 @Fe 3 Se 4 The composite material of @Se was calcined in a protective atmosphere to obtain a composite structure of Fe 3 O 4 @Fe 3 Se 4 Electrode material.

2. The method according to claim 1, It is characterized in that The iron source is one or more of ferric chloride, ferric nitrate, ferrous chloride and ferrous nitrate.

3. The method according to claim 1, It is characterized in that The selenium source is one or more of selenium dioxide, sodium selenate, selenic acid and selenium powder.

4. The method according to claim 1, It is characterized in that The molar ratio of the iron source to the selenium source is 2:(1~3).

5. The method according to claim 1, It is characterized in that The ratio of hydrazine hydrate to iron source is 2 mmol: (5~15ml).

6. The method according to claim 1, It is characterized in that The hydrothermal reaction temperature is 160-200°C; the reaction time is 12-24h.

7. The method according to claim 1, It is characterized in that The protective atmosphere is any one of nitrogen, argon, and argon-hydrogen mixed gas.

8. The method according to claim 1, It is characterized in that The calcination temperature is 400±20℃; the calcination time is 2~4h.

9. Fe with composite structure prepared by any method of claim 1-8 3 O 4 @Fe 3 Se 4 Electrode material.

10. Fe with a composite structure prepared by any method of claims 1-8 3 O 4 @Fe 3 Se 4 The electrode material is used as a sodium ion negative electrode material.